The Restoration chapter in the history of English law reform. Issue 1 (2nd January 2016) - Shapiro, Barbara J.
Abstract : This article attempts to show that both the Restoration era law reform efforts (1660-1688) were part of a long term tradition. It examines reforming efforts that began as least as early as the reign of Henry VIII and extended well into the eighteenth century. Whether or not law reform proposals became law, and most did not, early modern English parliaments were at the center of law reform efforts. It emphasizes the continuity of complaints, the similar nature of reform bills offered and the difficulty of transforming them into statutes. It argues that the desire for and the inability to achieve law reform was a characteristic of the entire early modern period, rather than a lamentable failure of the revolutionary era.